Trialkylammonium salt degradation: implications for methylation and cross-coupling. Issue 20 (20th April 2021) - Washington, Jack B.; Assante, Michele; Yan, Chunhui; McKinney, David; Juba, Vanessa; Leach, Andrew G.; Baillie, Sharon E.; Reid, Marc
Abstract : The dual reactivity of N, N, N -trimethylanilinium salts towards arylation and methylation is decoupled in this mechanistic investigation to enable more strategic application of these salts in either reaction class. Abstract : Trialkylammonium (most notably N, N, N -trimethylanilinium) salts are known to display dual reactivity through both the aryl group and the N -methyl groups. These salts have thus been widely applied in cross-coupling, aryl etherification, fluorine radiolabelling, phase-transfer catalysis, supramolecular recognition, polymer design, and (more recently) methylation. However, their application as electrophilic methylating reagents remains somewhat underexplored, and an understanding of their arylation versus methylation reactivities is lacking. This study presents a mechanistic degradation analysis of N, N, N -trimethylanilinium salts and highlights the implications for synthetic applications of this important class of salts. Kinetic degradation studies, in both solid and solution phases, have delivered insights into the physical and chemical parameters affecting anilinium salt stability. 1 H NMR kinetic analysis of salt degradation has evidenced thermal degradation to methyl iodide and the parent aniline, consistent with a closed-shell SN 2-centred degradative pathway, and methyl iodide being the key reactive species in applied methylation procedures. Furthermore, the effect of halide and non-nucleophilic counterions on salt degradation has been investigated, along with deuterium isotope and solvent effects. New mechanistic insights have enabled the investigation of the use of trimethylanilinium salts in O -methylation and in improved cross-coupling strategies. Finally, detailed computational studies have helped highlight limitations in the current state-of-the-art of solvation modelling of reaction in which the bulk medium undergoes experimentally observable changes over the reaction timecourse.